Underground taming of floods for irrigation (UTFI) in the river basins of South Asia: institutionalising approaches and policies for sustainable water management and livelihood enhancement - Reddy, V.R.; Pavelic, Paul; Hanjra, Munir A. (IWA Publishing, 2018)
Underground taming of floods for irrigation (UTFI) is a new approach for mitigating flood impacts through targeted floodwater storage in depleted aquifers for irrigating crops in the dry season. UTFI not only fosters the much desired conjunctive use and management of water resources but also provides the environmental services that are of high socioeconomic value. UTFI interventions are individually established at the local scale (e.g. village pond, check dam) but to achieve more substantial positive benefits at the scale of meso watersheds (10 s of km2) or sub-basins (100–1,000 s of km2) in the flood-prone river basins requires area-based implementation. Given the nature and scale required, UTFI needs to be managed at the community level with the help of appropriate institutional arrangements taking into account both the upstream and downstream locations. This paper reviews the existing institutional approaches and proposes an institutional framework that can help to mainstream UTFI management in the context of South Asia. The proposed model is centred on the existing formal institutions and also integrates non-market (participatory) and market (payment for ecosystem services) instruments that can provide win–win strategies for water resource management to downstream and upstream communities.